ANALISIS KUALITATIF DOKUMEN REKAM MEDIS RAWAT INAP DIARE AKUT BALITA DI RUMAHSAKITISLAMMASYITHOH BANGIL KABUPATEN PASURUAN TAHUN 2016 - Faiqatul Hikmah; Rossalina Adi Wijayanti; Nur Hidayah (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2018)
Acute diarrhea is on the first rank of 10 major diseases at the inpatient installation of RSI Masyithoh Bangil Pasuruan in 2015and also on the second rank in 2014. The problems that occur are the low completeness and consistency of medical record document of toddler’s acute diarrhea at RSI Masyithoh Bangil Pasuruan in 2016. The purpose of this research is to analyze the qualitative document of hospitalization medical record on toddler’s acute diarrhea at RSI Masyithoh Bangil Pasuruan in 2016. The type of this research is qualitative research and data collection technique used are observation, interview, and documentation. The population in this research was 272 DRM toddler’s acute diarrhea, with the total sample of 82 DRM. The results of this research are, incompatibilities and incompleteness of DRM toddler’s acute diarrhea at RSI Masyithoh Bangil Pasuruan especially in terms of qualitative medical history, physical examination, action or therapy, and home status. Utilization of extra information is recorded correctly. Health personnel are advised to complete DRM immediately after completion of the action or examination. And the need to do evaluation in improving the quality of inpatient medical records, especially on toddler’s acute diarrhea is in the completeness and consistency of qualitative data on medical record documents.